Rapid maxillary expansion compared to surgery for assistance in maxillary face mask protraction - (:unkn) unknown (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2011)
Objective: To compare the treatment outcomes of rapid maxillary expansion (RME) plus face mask (FM) and Le Fort 1 osteotomy + FM during maxillary protraction. Materials and Methods: This study was carried on 34 patients all having maxillary retrognathic, anterior cross-bite, Class III skeletal and dental malocclusion characteristics and a concave profile. Eighteen patients with milder maxillary retrognathism were treated with RME + FM. Sixteen other patients with moderate to severe maxillary retrognathism were treated with an incomplete Le Fort 1 osteotomy + FM therapy. Cephalometric data were evaluated statistically. Results: Significantly higher values of maxillary advancement and reduced treatment time were achieved with surgically assisted FM therapy. Conclusions: The surgically assisted FM treatment was more rapid and effective in maxillary protraction compared to the RME + FM treatment. (Angle Orthod. 2011;81:42-49.)
Keywords: Maxillary protraction; Face mask; Surgery; DISTRACTION OSTEOGENESIS; CLEFT-LIP; GRADUAL DISTRACTION; MIDFACE ADVANCEMENT; PALATE; CHILDREN; THERAPY